2010
DOI: 10.1089/pop.2009.0058
|View full text |Cite
|
Sign up to set email alerts
|

Acute Care for the Elderly: A Literature Review

Abstract: Traditionally, acute medical care has been insufficient to meet the complex care needs of frail older adults. The purpose of this study was to evaluate the effectiveness of Acute Care for the Elderly (ACE) units at improving hospitalization outcomes for adults older than 65 years of age. A review of the literature was performed, focusing on randomized controlled trials, clinical trials, reviews, and meta-analyses from 1990 to 2008. This review revealed ACE to be associated with positive global outcomes (eg, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 17 publications
3
46
2
Order By: Relevance
“…Our centre will be exploring how to improve outcomes by examining new care models, such as acute care for the elderly (ACE) units applied to a surgical setting where there is a focus on screening for early identification of geriatric syndromes, family and caregiver involvement at all stages of care, interdisciplinary assessments and an environment supportive of discharge planning and community services. [15][16][17] Our study reinforces that higher ASA class is associated with mortality following emergency general surgery in elderly patients. It should be mentioned that despite being a statistically significant variable, the ASA class had a wide CI, likely associated with our relatively small data set, and therefore we cannot accurately describe the direct magnitude of its effect on mortality.…”
Section: Discussionsupporting
confidence: 80%
“…Our centre will be exploring how to improve outcomes by examining new care models, such as acute care for the elderly (ACE) units applied to a surgical setting where there is a focus on screening for early identification of geriatric syndromes, family and caregiver involvement at all stages of care, interdisciplinary assessments and an environment supportive of discharge planning and community services. [15][16][17] Our study reinforces that higher ASA class is associated with mortality following emergency general surgery in elderly patients. It should be mentioned that despite being a statistically significant variable, the ASA class had a wide CI, likely associated with our relatively small data set, and therefore we cannot accurately describe the direct magnitude of its effect on mortality.…”
Section: Discussionsupporting
confidence: 80%
“…A recent review conducted by Ahmed et al showed that acute care for the elderly units are associated with reduced functional decline, costs, hospital length of stay, and lower readmission rates to acute care hospitals compared with usual care [35]. The results of the prevalence and reduction of delirium were mixed.…”
Section: Strategies To Cope With the Burden Of Elderly Patients Who Rmentioning
confidence: 99%
“…Traditionally, acute medical care has been insufficient to meet the complex care needs of frail older adults 30. These units are in hospital wards with protocols to ensure that elderly patients are thoroughly evaluated for potential iatrogenic problems before they occur, and any such problems are identified and appropriately managed 13.…”
Section: Preventionmentioning
confidence: 99%